Research on the Production of Coal Briquettes on the Basis of Crushing Industrial Waste - Qobilov Kh.X; Juraev J.M (Genius Journals, 2022)
Nowadays, the demand for solid fuel products in the country is growing day by day. However, in the production of solid fuel products, including the production of briquettes based on the fine fraction of coal and biocomposites, it is first necessary to address the issues of increasing its heat transfer efficiency. To do this, an in-depth analysis of the physical and mechanical properties of the selected raw materials, the degree of grinding, the laws of structural dependence, the basis for the introduction of targeted technologies. One of the main raw materials in briquette production is coal fraction.
Keywords: Coal fraction; grinding method; grinding process; coal briquettes